Acute Hormonal and Inflammatory Responses following Lower and Upper Body Resistance Exercises Performed to Volitional Failure - Chycki, Jakub; Krzysztofik, Michał; Sadowska-Krępa, Ewa; Baron-Kaczmarek, Daria; Zając, Adam; Poprzęcki, Stanisław; Petr, Miroslav (International journal of molecular sciences, 2024)
This study aimed to investigate the effects of a single bench press (BP) vs. leg press (LP) resistance training sessions on testosterone, cortisol, C-reactive protein (CRP) interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) concentrations, and creatine kinase (CK) activity in strength-trained males. Eleven strength-trained males participated in a cross-over randomized trial, undergoing two experimental sessions each consisting of five sets of the BP or the LP exercise to volitional failure with a load corresponding to 50% of one-repetition maximum. Blood samples were taken at baseline (BA), immediately post (POST), and 1 h after the cessation of exercise (POST-1). A significant increase in IL-6 concentration from BA to POST-1 was observed during the LP condition (p = 0.004; effect size [ES] = 0.64). Additionally, a significant main effect of time was found for increasing testosterone concentrations from BA to POST exercise (p = 0.014; ES = 0.25). A significantly lower cortisol concentration at POST-1 compared to POST (p = 0.001; ES = 1.02) was noted in the BP condition. Furthermore, a significantly lower cortisol concentration was found at POST-1 in the BP compared to the LP condition (p = 0.022; ES = 1.3). A significant increase in CK activity was reported from BA to POST (p = 0.024; ES = 0.69) and POST-1 (p = 0.045; ES = 0.55) during the LP condition, and from BA to POST-1 (p = 0.014; ES = 0.96) during the BP condition. No significant differences were found in the CRP (p = 0.659) and TNF-α concentrations (p = 0.487). These results suggest that the amount of muscle mass engaged during the resistance exercise may influence the changes in IL-6 and cortisol concentrations. Larger muscle groups, as engaged in the LP, more likely lead to elevated concentrations of IL-6 myokine.
Keywords: hydrokortison; Creatine Kinase; klinické křížové studie; Cross-Over Studies; Interleukin-6; odporový trénink; C-reaktivní protein; zánět; lidé; testosteron; Adult; dospělí; Inflammation; Testosterone; Male; mladý dospělý; Humans; TNF-alfa; mužské pohlaví; C-Reactive Protein; Young Adult; interleukin-6; Tumor Necrosis Factor-alpha; kreatinkinasa; Hydrocortisone; Resistance Training